Cooperative behaviour in rural Uganda: Evidence from the Uganda National Household Survey 2005 - Hill, Ruth Vargas; Bernard, Tanguy; Dewina, Reno (International Food Policy Research Institute, 2008)
This paper examines the extent of cooperative behaviour in rural Uganda as recorded in the most recent nationally representative household survey. Summary statistics on the presence of marketing cooperatives, recently formed National Agricultural Advisory Services farmers' groups, and risk sharing networks are presented. The determinants of the existence of marketing cooperatives and a farmer's decision to participate in newly formed groups are explored. Initial results indicate civil conflict, ethnic homogeneity and reported levels of trust have some impact in determining the presence of marketing cooperatives and the propensity of farmers to participate in newly formed groups.